Pengaruh Upah Minimum, Inflasi dan Pertumbuhan Ekonomi Terhadap Penyerapan Tenaga Kerja di Provinsi Sumatera Barat - Cahyanda Nofrita; Marwan Marwan (Universitas Negeri Padang, 2022)
The purpose of this study for knows does the minimum wage, inflation and economic growth have a significant effect on labor absorption in West Sumatera Province. This type of research of descriptive and associative with a quantitative approach. the data used is secondary data from 1990-2020. Data collection was carried out using documentation techniques obtained from the BPS. This study uses the SPSS 16.0 application with multiple regression analysis techniques and this model is free from classical assumption. The research result obtained are (1) Together minimum wage, inflation and economic growth significant effect on labor absorption in West Sumatera Province. (2) In the minimum wage the value of t-count > t-table which means that the minimum wage significant effect on labor absorption in West Sumatera Province. (3) Inflation the value of t-count < t-table which means that the inflation insignificant effect on labor absorption in West Sumatera Province. (4) economic growth the value of t-count < t-table which means that the economic growth insignificant effect on labor absorption in West Sumatera Province.